Guardians of the galaxy : Mother Entropy - Starlin, Jim (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2017)
When the Guardians are entrusted with an important but seemingly straight-forward delivery, nothing can go wrong, right? Right! Until everything starts going very wrong. Things might get a little more chaotic when the team meets the mysterious Mother Entropy: Who is she and what is her business with the Guardians?